NEW PUBLIC MANAGEMENT ACCORDING TO THE GOOD GOVERNANCE OF THE DEPARTMENT OF PHYSICAL EDUCATION - Trachuwanitch, Lertpan; Adultutra, Suchart; Maitreesophon, Bampen (Journal of MCU Phetchaburi Review, 2025)
This mixed-method research aimed to 1) study the level of new public management of the Department of Physical Education, 2) compare opinions towards new public management based on the principle of good governance classified by personal factors, 3) study the relationship between good governance and new public management of the Department of Physical Education, and 4) study the new public management approach based on the principle of good governance of the Department of Physical Education. The sample consisted of 140 personnel of the Department of Physical Education and 9 key informants. Data were analyzed using percentages, means, standard deviations, one-way variance, multiple regression, and content analysis. The results of the study found that 1) new public management was at a high level overall and in each aspect. 2) Different personal characteristics, including gender, age, marital status, highest level of education, average monthly income, and length of employment, had no different opinions towards new public management. 3) Good governance, participation, and transparency had a causal relationship with new public management. Statistically significant at the 0.001 level. 4) New approaches to public management according to the principles of good governance found that there should be collaboration between the public and private sectors. Communication and public relations strategies should be adjusted by using marketing approaches from the private sector. There should be a clear vision and goals that can be measured using KPIs to evaluate results. There should be public relations on social media. There should be discipline in the use of resources. There should be a system to control and inspect the use of office materials and equipment.